Liver Regeneration after Partial Hepatectomy Is Not Impaired in Mice with Double Deficiency of Myd88 and IFNAR Genes - Javier Vaquero; Kimberly J. Riehle; Nelson Fausto; Jean S. Campbell (Gastroenterology Research and Practice, 2011)
Liver regeneration is known to occur in mice lacking one or more Toll-like receptors (TLRs) or the adaptor protein MyD88. Though MyD88 is required for signaling by many TLRs, others signal via MyD88-independent pathways, leading to the induction of type I interferons (IFNs). Here, we assessed liver regeneration after partial hepatectomy (PH) in mice lacking both MyD88 and the type I IFN receptor (Myd88-IFNAR double-KO). Approximately 28% of Myd88-IFNAR double-KO mice had gross liver lesions prior to surgery. In mice without lesions, Myd88-IFNAR deficiency abrogated the increase in circulating IL-6 after PH but did not impair hepatocyte BrdU incorporation, mitotic figure counts, or recovery of liver-to-body weight ratios. These results indicate that type I IFNs are not responsible for the preservation of liver regeneration in Myd88-deficient mice, and they also cast doubt on the idea of microbial products being essential triggers of liver regeneration in mice undergoing PH.